Home and Leisure Accidents in children and young people from 0 to 19 years old in Portugal 2018. (30th September 2020) - Alves, T; Rodrigues, E; Mexia, R; Neto, M; Matias-Dias, C
Abstract: Background: Injuries and accidents are a challenge for public health considering their impact on victims and their families, especially in the younger, and also the potential for prevention and predictability. Due to specific characteristics of children and young persons related to the need of exploration and curiosity injuries namely those occur in domestic and leisure time, including the school setting are a topic of particular interest and study. This study aimed to characterize the occurrence of Home and Leisure Accidents (HLA) using hospital Emergency Department (ED) registered in EVITA system, in victims between 0 and 19 years old considering the injury mechanism, place of occurrence and products involved in the accident, in 2018, in Portugal. Methods: Were analysed data from the EVITA system, fed by the HLA registry at the ED of the Hospitals National Health that participate in this system. The frequency and distribution of HLA were analysed according to the injury mechanism, place of occurrence and products involved. Results and Discussion: In 2018, there were 38 528 ED attendances due to HLA 35, 0% of the victims were between 10-14 years old; 23, 7% had 5-9 years; 22, 8% between 15 and 19 years old and 18, 5% had under 4 years old. The results show more frequently HLA in males (59, 0%) than in females (41, 0%). In children under 4 years old 67, 8% of the HLA occurred at home, due to fall (68, 6%), having as products most involved the bed (10, 2%) and chair or bench (7, 5%). Between 5 and 9 years old, most HLA occurred at school (44, 5%) due to fall (62, 9%), involving ball (15, 1%) and scooter/tricycle/bike (6, 8%). In young people between 10 and 19 years old 47, 7% of HLA occurred at school, due to fall (54, 6%), having as main agents involved ball (28, 7%) and scooter/tricycle/bike (20, 3%). This information reinforces the importance of this problem but it is necessary future lines of research in order to point out the determinants of this mechanisms of injury. Key messages: The National Injury Surveillance System provides information that allows to know the characteristics and underlying causes of HLA that occur in children and young people. These data provide useful information for public health professionals working in the field of injury prevention among this vulnerable group of young people.